Factors Affecting Schools’ Acceptance of Platform SIPLah Implementation Using UTAUT Modified Model - Dini Anggraeni; Anna Fariyanti; Eko Ruddy Cahyadi (International Journal of Social Service and Research, 2023)
SIPLah is an inventive process for purchasing goods and services in educational institutions. It facilitates the reporting process by providing online marketplace partners, non-cash electronic payments, and digitization of documents. The purpose of this study is to examine the impact of SIPLah adoption on the quality of good government governance and identify the factors influencing educational institutions in adopting SIPLah. The study was conducted with 210 respondents, who are school principals or officially appointed individuals responsible for procuring goods/services. Questionnaires were distributed online, and data were analyzed using Structural Equation Model (SEM). The results show that Use Behavior in SIPLah adoption significantly influences good government governance. Performa expectancy, effort expectancy, and perceived service quality significantly influence attitude towards SIPLah adoption and usage. Conversely, social influence, facilitating condition, Trust in application, and perceived risk do not significantly affect attitude in adopting SIPLah.